2003
DOI: 10.1073/pnas.0438011100
|View full text |Cite
|
Sign up to set email alerts
|

JNK phosphorylation of Bim-related members of the Bcl2 family induces Bax-dependent apoptosis

Abstract: The c-Jun NH2-terminal kinase (JNK) is activated when cells are exposed to environmental stress, including UV radiation. Gene disruption studies demonstrate that JNK is essential for UV-stimulated apoptosis mediated by the mitochondrial pathway by a Bax͞Bak-dependent mechanism. Here, we demonstrate that JNK phosphorylates two members of the BH3-only subgroup of Bcl2-related proteins (Bim and Bmf) that are normally sequestered by binding to dynein and myosin V motor complexes. Phosphorylation by JNK causes rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
712
3
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 970 publications
(745 citation statements)
references
References 40 publications
25
712
3
5
Order By: Relevance
“…We also show that the Bmf induction was caused by histone hyperacetylation and siRNA-mediated knockdown of Bmf induction strongly reduced HDAC inhibitormediated apoptosis. Since JNK phosphorylates and activates Bmf by sequestering it from dynein light chain 2 (DLC2), 24 it may also be involved in the apoptotic process, but our results represent transcription activation as an additional mechanism for Bmf activation, and explain, at least in part, how HDAC inhibitors induce apoptosis.…”
Section: Introductionmentioning
confidence: 74%
“…We also show that the Bmf induction was caused by histone hyperacetylation and siRNA-mediated knockdown of Bmf induction strongly reduced HDAC inhibitormediated apoptosis. Since JNK phosphorylates and activates Bmf by sequestering it from dynein light chain 2 (DLC2), 24 it may also be involved in the apoptotic process, but our results represent transcription activation as an additional mechanism for Bmf activation, and explain, at least in part, how HDAC inhibitors induce apoptosis.…”
Section: Introductionmentioning
confidence: 74%
“…37,38 Stress-activated signaling such as the c-Jun N-terminal kinase 1 pathway can phosphorylate Bim, resulting in release from microtubules and induction of apoptosis. 39 As the onset of mitosis triggers the global disassembly of the microtubule network in preparation for assembly of the mitotic spindle, this would also result in widespread release of sequestered Bim. Induction of Bim degradation may therefore be a mechanism to cope with the sudden release of cytoskeleton-associated Bim during mitosis.…”
Section: Discussionmentioning
confidence: 99%
“…A notable exception is a landmark study 25 on the context dependence of the Jun-activated kinase (JNK) in apoptosis. Before this work, paradoxical results suggested that JNK had a proapoptotic function 26 , an anti-apoptotic function 27 or even a lack of involvement in apoptosis 28 . The systematic approach undertaken by Janes et al 25 revealed that the phosphorylation status of JNK (and thus its catalytic activity) was not sufficient to determine apoptotic commitment; instead, activation of JNK could lead to both apoptosis and proliferation depending on the cellular signaling network state at the time of activation.…”
Section: From Genomic Lesions To Functional Network Perturbationsmentioning
confidence: 95%